Turf planting device for garden maintenance - LI XIAOGUANG; QU LI; WANG SHUBIAO; HU ZHENYUAN; ZHAO HUI; ZHANG CHUANHUI; AI CHUNXIAO (2024)
The invention belongs to the technical field of forestry, in particular to a turf planting device for garden maintenance, and provides the following scheme that the turf planting device comprises a base, moving wheels are arranged at four corners of the bottom of the base, a plurality of supporting rods are connected to one side of the top of the base through bolts, and a conveying mechanism is arranged among the supporting rods; a discharging opening is formed in the top of the base, a discharging mechanism is arranged on one side of the discharging opening and located below one side of the conveying mechanism, a water tank is connected to one side of the top of the base through bolts, a sealing cover is connected to the top of the water tank through bolts, and a water pump is connected to the top of the sealing cover through bolts. According to the device, the turf discharging effect is conveniently improved, the situation that turf is adhered to the surface of the discharging mechanism due to friction in t